FRI0585 Nailfold Videocapillaroscopy: An Open Window on Coronary Microvascular Dysfunction in Systemic Sclerosis. (9th June 2015) - Zanatta, E.; Pigatto, E.; Famoso, G.; Polito, P.; Miatton, P.; Schiavon, F.; Punzi, L.; Cozzi, F.; Tona, F.
Abstract : Background: Cardiac involvement is an important determinant of prognosis in systemic sclerosis (SSc). The identification of patients with high risk has a great importance and coronary microvascular dysfunction (CMD) predicts major adverse outcomes in several cardiovascular diseases (1). Nailfold video capillaroscopy (NVC) represents an essential tool in the classification criteria for SSc and the best method to analyse microvascular abnormalities in these patients. Objectives: To assess the relationship between nailfold capillaroscopy-derived scores and coronary flow reserve (CFR), a marker of CMD, in SSc. Methods: Twenty-three patients (20 F, 3 M, aged 59±12 years), 13 with diffuse and 12 with limited form of SSc, without clinical evidence of heart disease, and 23 healthy controls were enrolled. All patients underwent NVC. According to Sulli et al. the capillaroscopic parameters considered were: presence of enlarged and giant capillaries, haemorrhages, loss of capillaries (avascular score), microvascular disarray, and capillary ramifications. For each field was adopted a semiquantitative rating scale to score each capillary abnormality (1). Coronary flow velocity in the left anterior descending coronary artery was detected by transthoracic Doppler echocardiography (TDE) at rest and during adenosine infusion. CFR was the ratio of hyperaemic diastolic flow velocity (DFV) to resting DFV. A CFR≤2.5 was considered abnormal and marker of CMD. Results: CFR was lower in patients with SSc than in healthy controls (2.2±0.8 vs 3.6±0.6, p<0.0001). The prevalence of CMD was higher in patients than in controls (65% vs 4%, p<0.0001). CFR was inversely related to avascular score (Figure A ) and capillary ramification (r=-0.473, p=0.02). In patients with CMD (CFR≤2.5) avascular score was higher (0.78±0.06 vs 0.22±0.1, p=0.02) (Figure B ). No relationship with other NVC scores was found. An exploratory receiver-operator characteristic analysis identified avascular score>0.27 (AUC 0.80, p=0.01) as the best discriminating threshold for CMD (Sensitivity 73%, Specificity 75%, NPV 60%, PPV 84%; OR 2.93, p=0.02). Conclusions: Our study showes that microvascular abnormalities at NVC correlate with CMD in SSc. The evaluation of NVC in SSc might represent a tool for the prediction of coronary microvascular dysfunction, by considering the systemic microvascular derangement at the capillary nailfold. References: Pepine CJ et al. JACC 2010. Sulli A et all. Ann Rheum Dis 2008. Disclosure of Interest: None declared